Predicting eye movement patterns from fMRI responses to natural scenes - Thomas P. O’Connell (Nature Portfolio, 2018)
Human eye movements when viewing scenes can reflect overt spatial attention. Here, O’Connell and Chun predict human eye movement patterns from BOLD responses to natural scenes. Linking brain activity, convolutional neural network (CNN) models, and eye movement behavior, they show that brain activity patterns and CNN models share representations that guide eye movements to scenes.